Analysis of Factors Influencing the Application of Accounting Information Systems in UMKM, Dimsum, Seceng Pajaresuk, Pringsewu - Sawitri, Riska Agi; Nurzanah, Eka; Sari, Selly Puspita; Dahrul, Annida; Harlianty, Rully Afrita; Mukhlis, Hamid; Imelda, Vivi (Utan Kayu Publishing, 2022)
This study aims to determine the factors that influence the application of accounting information systems in UMKM Dimsum Seceng Pajaresuk, Pringsewu. The research was conducted using qualitative methods, the researchers analyzed the data and information obtained from interviews and observations. The subject of this research is UMKM Dimsum Seceng Pajaresuk Pringsewu. The results showed that UMKM Dimsum Seceng Pajaresuk Pringsewu had not implemented an accounting information system due to factors namely limited capital, limited human resources, weak business networks and capabilities, limited business facilities, and infrastructure. This has caused UMKM Dimsum Seceng Pajaresuk to not be able to use the accounting information system.